Studi Komunitas Tumbuhan Di Kawasan Cagar Alam Morowali Propinsi Sulawesi Tengah - Ismet Khaeruddin (Biocelebes, 2008)
The study about plant community in the vicinity of Taronggo village, Morowali Nature Reserve has been conducted from May to June 2007. The research aimed was to study diversity of plant by using plot line transect methods along 3000 m with 43 nested subplots 10 by 10 m in size. Formula of Dumbois-Muller and Ellenberg was followed to analyse the vegetation data . The results showed that the studied area was very rich with plant biodiversity with Shannon diversity Index was more than 3. I recorded 62 species of tree, 43 species of poles, 50 of saplings and 68 species of seedling and understorey plant. The highest of Importance Value Index (IVI) of tree was Manilkara fasciculata Laam & Maas (Sapotaceae) with value 31.48%, poles was Ficus sp (Moraceae) with value 41.02%, saplings was Ficus sp (Moraceae) 34.50% and seedling or understorey plant was “lauro sambuta” (Calamus minahasae Becc/Arecaceae) with value 31.48%. Moreover, several endemic and unique plants were recorded from the studied area of the Morowali NR such as Sarcotheca celebica Veldk. (Oxalidaceae), Deplancea bencana L. (Bignoniaceae), Palaquium maliliensis van Royen (Sapotaceae), Macadamia hildebrandii Steenis (Proteaceae), Gronophyllum macrospadix, Korthalsia celebica Becc. (Arecaceae), Knema celebica de Wilde (Myristicaceae) etc. Key words : Plant community, Morowali Nature Reserve, Central Sulawesi, Endemic.